Chemistry of deltahedral Zintl ions - Sevov, S; Goicoechea, J (2006)
This review focuses on the reactivity of nine-atom deltahedral clusters of group 14, also known as deltahedral Zintl ions, toward various main-group and transition-metal compounds. The redox chemistry of these species and their ability to form oligomers, polymers, and functionalized clusters are discussed, and the cluster geometries, their bonding, and electronic structures are described. © 2006 American Chemical Society.